Age constraints on c. 1.9 Ga volcanism, basin evolution and mineralization at the world-class Zinkgruvan Zn-Pb-Ag(-Cu) deposit, Bergslagen, Sweden - Jansson, Nils F.; Simán, Filip; Allen, Rodney L.; Mansfeld, Joakim; Kampmann, Tobias C. (Precambrian Research, 2023)
We present improved age constraints for the world-class Zinkgruvan Zn-Pb-Ag and Cu deposit: one of the largest Zn deposits of the Fennoscandian shield, and one of the earliest large, basin-hosted Zn deposits that formed from oxidized saline brines. Secondary Ion Mass Spectrometry (SIMS) U-Pb dating on zircon is used to constrain at least two phases of c. 1.9 Ga volcanism in the Zinkgruvan area, separated by a period of fluvial sedimentation, all of which predated formation of the stratiform Zn-Pb-Ag mineralization. A 1908 ± 4 Ma age for a rhyolitic rock of the first volcanic phase is the oldest recorded U-Pb zircon age of a volcanic rock in the Bergslagen lithotectonic unit (BLU) where Zinkgruvan is located. Similarly, two identical ages of 1898 ± 5 Ma for volcanic rocks belonging to the second volcanic phase indicate that the local volcanic activity, which formed the stratigraphic footwall, ended earlier in the Zinkgruvan area than in other parts of the BLU, where intense explosive felsic volcanic and intrusive activity until c. 1891 Ma has been demonstrated. This, along with a hybrid siliciclastic-volcaniclastic (tuffitic) character of the Zinkgruvan ore host, confirms earlier interpretations that the Zinkgruvan deposit formed in an actively subsiding basin, distal to active volcanic centers in the BLU in the time range 1.90–1.89 Ga. Our results support models suggesting that basinal brine-driven hydrothermal systems in sedimentary basins distal to volcanic centers could form world-class Zn deposits as early as c. 1.90 Ga. Validerad;2023;Nivå 2;2023-07-06 (hanlid)